PERCEPTION AND MOTIVATION OF STUDENTS ON EFL LEARNING THROUGH YOUTUBE - Marini, Marini putri; Frida Dini Chaerunisa; Muhammad Dewa Prasetya; Naf'an tarihoran (Jurnal Ikhtibar Nusantara, 2026)
This study is grounded in the fast advancement of digital technology, which has influenced English as a Foreign Language (EFL) learning, with YouTube becoming a popular platform due to its accessibility and audiovisual features. This study aims to investigate students’ perceptions and motivations toward EFL learning through YouTube. A quantitative descriptive method was employed, involving 150 students from the English Education Department. The data were collected using a structured questionnaire distributed through Google Form and analyzed using descriptive statistics, including mean, median, mode, and standard deviation. The findings reveal that students have positive perceptions of YouTube as a learning medium, with mean scores ranging from 3.85 to 4.21, indicating that YouTube is engaging, accessible, and helpful in understanding learning materials. In addition, YouTube significantly enhances students’ motivation, encouraging them to practice English skills and engage in autonomous learning outside the classroom. These results indicate that YouTube is an effective medium for supporting EFL learning. The study implies that integrating YouTube into teaching practices can create more engaging, flexible, and student-centered learning environments while supporting students’ independent learning.